THE EFFECT OF WORK MOTIVATION, WORK ENVIRONMENT, AND COMPETENCE ON EMPLOYEE PERFORMANCE (A STUDY AT FROZEN EDAMAME COMPANY) - Aisha Rima; Novi Haryati; Anisa Aprilia (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
PT. Mitratani Dua Tujuh is required to be able to meet the market demand for frozen edamame due to its increasing demand. Therefore, productive human resources are needed, which can be seen through employee performance appraisals. This research aimed to analyze work motivation, work environment, and competence factors on the employee performance in frozen edamame company. The study was conducted at PT. Mitratani Dua Tujuh in Jember Regency from March-April 2020. The number of samples was 38 employees determined using a purposive sampling technique. The data were obtained by distributing questionnaires and analyzed using the partial least squares structural equation modeling (PLS-SEM) analysis. The results showed that work motivation (X1) had a positive effect on the employee performance variable (Y) of 0.43, with a P-value of < 0.01. In contrast, the work environment variable (X2) had a negative effect on performance (Y) of 0.26, with a P-value of 0.04. Furthermore, competence (X3) had a positive effect on performance (Y) of 0.39, with a P-value of < 0.01. The R- Squared value was 0.44. In conclusion, work motivation, work environment, and competence simultaneously affect employee performance by 44%, and the rest are affected by other variables outside the research model.